Trends in hospitalization and death rates among patients with head and neck cancer in Spain, 2009 to 2019 - Carlos Carazo-Casas; Ruth Gil-Prieto; Valentín Hernández-Barrera; Ángel Gil de Miguel (Taylor & Francis Group, 2022)
Background Head and neck squamous cell carcinoma (HNSCC) is the seventh most common cancer worldwide, and prevalence is still substantially higher in men than in women. Causative factors include smoking and alcohol use, while human papillomavirus (HPV) infection is causally related to a subset of oropharyngeal cancers. In this retrospective study, we aimed to provide estimates on the clinical and economic burden of HNSCC in Spain. Methods We used the discharge reports from the Spanish Minimum Basic Data Set (MBDS), to retrospectively analyze hospital discharge data in individuals with a diagnosis of HNSCC in any diagnostic position, based on the ICD coding system (ICD-9-CM and ICD10 CM), from 2009 to 2019. Results A total of 175,340 admissions and 14,498 deaths due to laryngeal, pharyngeal and oral cavity cancer were recorded in Spain, of which 85% occurred in men. The most prevalent diagnoses were laryngeal cancer in men (50.9%) and oral cavity cancer in women (49.1%). In general, the hospitalization and death rates for all major head and neck cancer sites decreased in men and increased or remained stable in women during the study period. However, the corresponding rates for tonsil cancer, strongly associated with HPV infection, increased significantly in men. Overall, the economic burden of HNSCC during the study period was estimated at 100 million euros per year on average. Conclusion HNSCC still places an important clinical and economic burden on the health system in Spain. Prevention strategies should be prioritized, and vaccination programs against HPV in both sexes should be reinforced.